Surgical treatment of moderate and severe hallux valgus: 30 cases undergoing surgery using the percutaneous Chevron technique - Silva, Rafael Ferreira da; Baptista, André Donato (Scientific Journal of the Foot & Ankle, 2018)
Objective: To evaluate the radiographic parameter correction and clinical improvement of moderate and severe hallux valgus deformities treated by percutaneous Chevron osteotomy. Methods: Twenty-six patients (30 feet) underwent surgery. The following were measured preoperatively and postoperatively: hallux metatarsophalangeal (MTP) angle, intermetatarsal angle between the 1st and 2nd metatarsals (IMA), distal metatarsal joint angle (DMJA) and pre- and postoperative AOFAS scores with a minimum of 6 months of follow-up. Results: The mean patient age was 52.3 years. Preoperatively, the mean AOFAS score was 45.6, which rose to 90.3 after the procedure, showing a statistically significant improvement. The preoperative mean MTP, IMA and DMJA angles were 29.7°, 14.2° and 14.2°, respectively, and the postoperative values were 12.8°, 8.2° and 11.1°, respectively. The improvements in MTP and IMA angles were also statistically significant. There were no losses in angular parameters or worsening of AOFAS scores during follow-up. Conclusion: The percutaneous Chevron surgical technique proved to be safe and effective for the correction of moderate and severe hallux valgus cases and achieved significant improvements in clinical and radiographic parameters and low rates of postoperative complications. Level of Evidence III; Retrospective Comparative Study.